The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/s2213-8587(17)30088-8
|View full text |Cite|
|
Sign up to set email alerts
|

Apolipoprotein(a) isoform size, lipoprotein(a) concentration, and coronary artery disease: a mendelian randomisation analysis

Abstract: SummaryBackgroundThe lipoprotein(a) pathway is a causal factor in coronary heart disease. We used a genetic approach to distinguish the relevance of two distinct components of this pathway, apolipoprotein(a) isoform size and circulating lipoprotein(a) concentration, to coronary heart disease.MethodsIn this mendelian randomisation study, we measured lipoprotein(a) concentration and determined apolipoprotein(a) isoform size with a genetic method (kringle IV type 2 [KIV2] repeats in the LPA gene) and a serum-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
132
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(142 citation statements)
references
References 30 publications
5
132
2
3
Order By: Relevance
“…6,14 LPA kringle IV type 2 repeats and raised lipoprotein(a) concentrations in serum have been associated with increased prevalence of coronary heart disease in a mendelian randomisation analysis. 26 The findings from previous studies and this analysis, therefore, support a causal link between lipoprotein(a) and atherosclerosis development.…”
Section: Discussionsupporting
confidence: 69%
“…6,14 LPA kringle IV type 2 repeats and raised lipoprotein(a) concentrations in serum have been associated with increased prevalence of coronary heart disease in a mendelian randomisation analysis. 26 The findings from previous studies and this analysis, therefore, support a causal link between lipoprotein(a) and atherosclerosis development.…”
Section: Discussionsupporting
confidence: 69%
“…8b). Our model ascribed greatest importance to rs10455872, a previously described SNP associated with KIV2-CN 14,15 . The full 61-variant model in our validation dataset explained 60% of variation in genotyped KIV2-CN (Supplemental Table 5, Supplemental Fig.…”
Section: Structural Variant Analyses: Discovery and Imputation Of Kivmentioning
confidence: 97%
“…Genetic variation at the LPA locus is an optimal instrument for Mendelian randomization (MR) as it strongly and specifically influences circulating Lp(a) levels. Past studies have performed Lp(a) MR across clinical and metabolic traits using genetic risk scores comprised of between 1-18 variants 14,39,40 . Here, we performed MR using three different genetic instruments per cohort to distinguish variant classes influencing Lp(a) phenotypes: 1) an expanded genetic risk score, "GRS," comprised of the sum of the KIV2-CN-adjusted variant effects from LD-pruned variants in a ~4MB window around LPA with sub-threshold significance (P < 1x10 -4 ); 2) a "KIV2-CN" score using the directly genotyped or imputed KIV2-CN; and 3) a combined "GRS+KIV2-CN" score combining scores from (1) and (2).…”
Section: Mendelian Randomizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Single nucleotide polymorphisms (SNP) at the LPA locus like rs10455872 and rs3798220 were also associated with an increased level of Lp(a) (13,14). Several studies using Mendelian randomization approaches have demonstrated that LPA variants were associated with the risk of coronary heart disease (CHD) and myocardial infarction (14)(15)(16)(17), which supports a causal role of Lp(a) in ischemic cardiovascular disease.…”
Section: Introductionmentioning
confidence: 89%